Family-Centered Care in the Intensive CareUnit—What Does Best Practice Tell Us? - Ludmir, Jonathan; Netzer, Giora (Seminars in Respiratory and Critical Care Medicine, 2019)
Families in the intensive care unit (ICU) experience high-stress levels and are at risk of developing psychological symptoms including depression, anxiety, and posttraumatic stress disorder (PTSD). Family-centered care defines an approach that encompasses respect, compassion, and support for families. By alleviating stress and anxiety, this approach can increase family satisfaction, improve communication with staff, and decrease ICU length of stay. Family-centered care relies on an interdisciplinary approach. Its components include daily family-centered rounds, frequent family meetings, and ensuring an adequate family support environment. Each of the components of family-centered care depend on adequately trained clinical staff who are champion in empathetic communication and constantly support family member throughout an ICU stay.
Keywords: family; empathy; depression; satisfaction